AIRBORNE LASER SCANNING STRIP ADJUSTMENT AND AUTOMATION OF TIE SURFACE MEASUREMENT - PFEIFER, NORBERT (Boletim de Ciências Geodésicas, 2005)
Airborne laser scanning of the earth surface and other objects on top it yields measurements of unstructured point clouds in a strip wise manner. Often multiple length strips with a small overlap are observed, sometimes augmented by a few cross strips for validation purposes. Due to inaccurate calibration of the entire measurement system and due to the limited accuracy of direct geo-referencing (i.e., the exterior orientation determination) with GPS and IMU, including systematic errors, adjacent strips may have discrepancies in their overlap. For removing these discrepancies strip adjustment algorithms require quantification on these offsets at various locations within the overlapping zones. Different methods of strip adjustment are reviewed, followed by the presentation of a general method for determining the discrepancies automatically. This method the core of the paper is based on segmenting the point cloud in the overlap. In the examples, mean offsets between neighboring strips in the order of a few centimeters are reconstructed. The offsets also show substantial variation along the strip. The method developed for discrepancy determination can be applied to height or full 3D strip adjustment and for approaches using the original measurements, the coordinates of the measured points, or only the offsets between surfaces. An example of strip adjustment using discrepancy observations with the method presented and a discussion of the results conclude this paper.